Students’ Investment Decisions with Intention as an Intervening Variable - Ummah, Afaful; Ahsan, Muhamad; Anas, Ahmad (EQUILIBRIUM, 2021)
This quantitative research aimed to determine the factors influencing students’ decisions to invest with intention as an intervening variable using the Partial Least Square (PLS) method through the smartPLS 3.0. The population in this study was UINSA students who already had accounts in GIS UINSA. The research sample of 110 respondents was selected using purposive sampling techniques. The results showed that intention influences students’ investment decisions. Returns and technological advancements influence their investment decision through intention, both directly and indirectly.Conversely, knowledge, motivation, and capital market training do not affect that, either directly or indirectly. Therefore, knowledge and Islamic capital market training need more attention. It can be done by optimizing the socialization and education about the Islamic capital market by holding seminars, training, webinar and providing facilities and tools that promote the motivation to invest in the Islamic capital market to influence the intention of students to invest.